Pendayagunaan Zakat Pada Masa Pandemi Covid-19 - Gebrina Rizki Amanda; Fatatun Malihah; Sulistiani Indriyastuti; Nur Khumairah; Tulasmi Tulasmi; Titania Mukti (Jurnal Ilmiah Ekonomi Islam, 2021)
At this time, the world is in an irregular and chaotic condition due to the covid-19 virus, especially in the economic sector. This resulted in the community's economy becoming paralyzed so that the income of the poor was also affected. To restore the state's condition, cooperation from various elements is needed, one of which is bias through zakat management institutions. The optimal utilization and management of zakat will help the community besides that the distribution is carried out appropriately and paying attention to the receiving groups so that the utilization is right on target. This research was conducted to analyze how the mechanism and implementation of zakat distribution in the response to the Covid-19 pandemic. The method used in this research is the literature study method. The literature study in this research is technical literature and non-technical literature. The results of the literature study can be used as input and a basis in explaining how the mechanism and implementation of zakat distribution in the response to a pandemic. Based on the analysis, BAZNAS has distributed zakat funds to three sectors, namely the health emergency sector, the socio-economic emergency sector, and the existing program sustainability sector. Not only that, BAZNAS and the Ministry of Religion also helped preachers who were affected by the Covid-19 virus. In the results of this analysis, it can be concluded that the handlers of zakat implementation in handling Covid 19 have a very big influence. The total distribution of funds for the three sectors reached Rp. 7,578,461,063. This zakat fund distribution is only valid in April, May, and June 2020.